Periodic variations in the ratio of free to thylakoid-bound chloroplast ribosomes during the cell cycle of Chlamydomonas reinhardtii (The Rockefeller University Press, 1976)
The ratio of free to thylakoid-bound chloroplast ribosomes in Chlamydomonas reinhardtii undergoes periodic changes during the synchronous light-dark cycle. In the light, when there is an increase in the chlorophyll content and synthesis of thylakoid membrane proteins, about 20-30% of the chloroplast ribosomes are bound to the thylakoid membranes. On the other hand, only a few or no bound ribosomes are present in the dark when there is no increase in the chlorophyll content. The ribosome-membrane interaction depends not only on the developmental stage of the cell but also on light. Thus, bound ribosomes were converted to the free variety after cultures at 4 h in the light had been transferred to the dark for 10 min. Conversely, a larger number of chloroplast ribosomes became attached to the membranes after cultures at 4 h in the dark had been illuminated for 10 min. Under normal conditions, when there was slow cooling of the cultures during cell harvesting, chloroplast polysomal runoff occurred in vivo leading to low levels of thylakoid-bound ribosomes. This polysomal runoff could be arrested by either rapid cooling of the cells or the addition of chloramphenicol or erythromycin. Each of these treatments prevented polypeptide chain elongation on chloroplast ribosomes and thus allowed the polyosomes to remain bound to the thylakoids. Addition of lincomycin, an inhibitor of chain initiation on 70S ribosomes, inhibited the assembly of polysome-thylakoid membrane complex in the light. These results support a model in which initiation of mRNA translation begins in the chloroplast stroma, and the polysome subsequently becomes attached to the thylakoid membrane. Upon natural chain termination, the chloroplast ribosomes are released from the membrane into the stroma.